The practicality of theory: Reciprocity, assessment and applied linguistics - Weideman, Albert (Stellenbosch Papers in Linguistics Plus, 2023)
In language assessment there is awareness that at a fundamental level it is a subfield of applied linguistics. Hence a productive understanding of that relationship is to ask, first, how we understand the discipline of applied linguistics and, second, how language assessment can, together with other subfields, be shown to belong to it. Employing the idea of applied linguistics as a discipline of design, we can identify at least three subfields. These involve the development of three prime applied linguistic artefacts: language policies and language management plans; language tests and assessments; and language curricula and courses. Abstracting and considering more closely their technical function and the nuclear meaning of design of that function, we may further investigate a number of technically stamped primitives or fundamental concepts. These derive from the coherence of the technical modality with other dimensions of reality, yielding the foundational concepts of homogeneity, range, reliability, validity, differentiation, sensitivity, rationality, meaningfulness, appropriateness, usefulness, alignment, accountability, fairness, and trustworthiness. From these fundamentals, in turn, emerge various principles of responsible design applicable to all three kinds of applied linguistic artefacts: policies, tests and courses. The three subfields not only have principles in common, but by virtue of that also have a reciprocal relationship: the one can learn design lessons from the other. This article will refer first to the notion of language assessment as subfield of applied linguistics, second to the principles of responsible design, and third to the reciprocity among applied linguistic designs as various as language policies, tests, and courses.